2007
DOI: 10.1056/nejmoa071453
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes after Repeat Doses of Antenatal Corticosteroids

Abstract: Children who had been exposed to repeat as compared with single courses of antenatal corticosteroids did not differ significantly in physical or neurocognitive measures. Although the difference was not statistically significant, the higher rate of cerebral palsy among children who had been exposed to repeat doses of corticosteroids is of concern and warrants further study. (ClinicalTrials.gov number, NCT00015002 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
157
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(173 citation statements)
references
References 29 publications
9
157
0
7
Order By: Relevance
“…Although the use of synthetic prenatal GCs to promote lung maturation in preterm infants is undisputed, clinical and preclinical studies have revealed the potential for prolonged or delayed side effects linked to antenatal or neonatal GC usage (5)(6)(7). In several species, including humans, these studies indicate that exogenous treatment with GCs during fetal or neonatal development or fetal exposure to high levels of endogenous GCs produced as a result of maternal stress can be associated with neurological, cognitive, and affective disorders that emerge later in childhood (7,8).…”
mentioning
confidence: 99%
“…Although the use of synthetic prenatal GCs to promote lung maturation in preterm infants is undisputed, clinical and preclinical studies have revealed the potential for prolonged or delayed side effects linked to antenatal or neonatal GC usage (5)(6)(7). In several species, including humans, these studies indicate that exogenous treatment with GCs during fetal or neonatal development or fetal exposure to high levels of endogenous GCs produced as a result of maternal stress can be associated with neurological, cognitive, and affective disorders that emerge later in childhood (7,8).…”
mentioning
confidence: 99%
“…С одной стороны, их применение в раннем неонатальном периоде уменьшает длительность искусственной вентиляции [51], с другой -сопряжено с увеличением концентрации глюкозы в кро-ви, замедлением набора веса и увеличением частоты таких клинических осложнений, как некротизирующий энтероколит [52]. Введение дексаметазона новорожден-ным крысам приводило к гипоплазии легких и легочной гипертензии [52].…”
Section: вопросы современной педиатрииunclassified
“…Por este motivo se sugirió como una buena práctica clínica, la repetición semanal de cursos de corticoides a las mujeres que luego de un primer curso de corticoides, permanecen en riesgo de parto prematuro. Las investigaciones de diseño retrospectivo pusieron en duda la seguridad y eficacia de esta práctica (4,5), y los estudios prospectivos randomizados hasta ahora publicados no permiten una conclusión definitiva (6). Es indispensable contar con estudios de diseño prospectivo que permitan responder si el uso de dosis repetidas de corticoides en mujeres en riesgo de parto prematuro, resultan en más beneficio que daño, o viceversa.…”
Section: Arelevancia Clínica De La Investigaciónunclassified